Balloon remodeling for aneurysm coil embolization with the coaxial lumen Scepter C balloon catheter: initial experience at a high volume center. (7th November 2012) - Spiotta, Alejandro M; Miranpuri, Amrendra; Hawk, Harris; Chaudry, M Imran; Turk, Aquilla S; Turner, Raymond D
Abstract : Introduction: The use of balloon remodeling allows for the treatment of aneurysms that were previously considered to be poor candidates for coil embolization. The Scepter C (Microvention, Tustin, California, USA) is a novel temporary occlusion balloon system with a dual coaxial lumen catheter. The design accommodates a more steerable 0.014 inch guidewire with improved control for delivery to the target lesion. We describe our initial experience with the use of this device for balloon remodeling to assist during aneurysm coil embolization. Methods: All aneurysms that were treated with balloon remodeling employing the Scepter C balloon at a single institution (Medical University of South Carolina) from the time it was available in October 2011 to July 2012 were evaluated. Patient demographics, aneurysm characteristics, procedural success, and adverse events were assessed. Results: 52 aneurysms were treated in 48 patients (45 women, three men) with a mean age of 59.3±11 years (mean±SD). Mean aneurysm height was 5.9±3 mm, width 4.4±2 mm with a 3.1±2 mm broad neck. A variety of aneurysms were treated. The most commonly utilized size was the 4 mm×10 mm (n=33) balloon. A Raymond 1 (complete occlusion) was achieved in the majority (n=44; 84.6%) of aneurysms, Raymond 2 (residual neck) in five, and Raymond 3 (residual aneurysm) in five. There was one complication (1.9%) attributed directly to balloon use. Conclusions: Our initial experience with the dual coaxial lumen Scepter C occlusion balloon catheter demonstrates its feasibility for use in balloon remodeling for aneurysm coil embolization. A variety of aneurysms at different locations were treated with satisfactory initial angiographic results and adverse event rates.